Correlation of Intensity of Use of Social Media with The Level of Social Anxiety In Adolescents - Zahrul Khafida Silmi; Wiwin Renny Rachmawati; Angga Sugiarto; Tulus Puji Hastuti (Midwifery and Nursing Research, 2020)
Background: Social media provides many positive impacts and ease of interaction, but not a few negative impacts, one of them was anxiety. Indonesia ranks 4th in the world in the used of social media with an average duration of usage for 8 hours 51 minutes every day. Though adolescence is an age where someone was very susceptible to anxiety. This anxiety if coupled with the high intensity of used of social media in adolescents was feared will have an effect on social interaction and cause anxiety to be higher and at risk of becoming social anxiety due to the lack of real communication to the social environment. The aims to find out the correlation between the intensity of the used of social media with the level of social anxiety in adolescentsMethods: This research used observational method with Cross Srectional design.Results: Based on the results of the data analysis test, the value of p = 0.00 (p 0.05) was obtainedConclusion: There was a correlation between the intensity of the used of social media and social anxiety